Teacher Intervention for Coping with Students’ Learning Difficulties of Madrasah Ibtidaiyah in the Covid-19 Social Restrictions - Enung Nugraha; Encep Syarifudin (UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractDue to the Covid-19 pandemic, the government implemented a large-scale social restriction policy that impacted online learning. There are obstacles where not all students have supporting learning facilities and have learning difficulties requiring teacher intervention in the learning process. The study aimed to determine teacher intervention in the learning process for students with learning difficulties. The research method used descriptive qualitative at Madrasah Ibtidaiyah (Islamic Elementary School) Ats-Tsauroh Serang City, Banten Province. Data collection was limited to interviews with eight informants, including teachers, madrasa heads, and deputy madrasa heads, during the social restrictions period in February-April 2021. The results showed that teacher intervention in overcoming student learning difficulties was carried out directly, namely by understanding student conditions, understanding the typology of student learning difficulties, communicating with students' parents, observing students' family environmental conditions, conducting study visits to students' homes, and assessing student motivation. Teacher creativity is essential in making decisions for the benefit of student learning so that teachers provide the best service under challenging conditions. The implication of this research is that teacher intervention is effective in overcoming students' learning difficulties in the Covid-19 social restrictions.Keywords: teacher intervention, learning difficulty, home visits.Â AbstrakAkibat pandemi Covid-19, pemerintah menerapkan kebijakan pembatasan sosial berskala besar yang berdampak pada pembelajaran daring. Terdapat kendala di mana tidak semua siswa memiliki fasilitas belajar yang mendukung dan mengalami kesulitan belajar yang memerlukan campur tangan guru dalam proses pembelajaran. Penelitian ini bertujuan untuk mengetahui intervensi guru dalam proses pembelajaran bagi siswa yang mengalami kesulitan belajar. Metode penelitian yang digunakan adalah deskriptif kualitatif di Madrasah Ibtidaiyah Ats-Tsauroh Kota Serang, Provinsi Banten. Pengumpulan data terbatas pada wawancara dengan delapan informan, termasuk guru, kepala madrasah, dan wakil kepala madrasah selama masa pembatasan sosial pada Februari-April 2021. Hasil penelitian menunjukkan bahwa intervensi guru dalam mengatasi kesulitan belajar siswa dilakukan secara langsung, yakni dengan memahami kondisi siswa, memahami tipologi kesulitan belajar siswa, berkomunikasi dengan orang tua siswa, mengamati kondisi lingkungan keluarga siswa, melakukan kunjungan belajar ke rumah siswa, dan menilai motivasi siswa. Kreativitas guru sangat penting dalam mengambil keputusan untuk kepentingan belajar siswa sehingga guru memberikan pelayanan terbaik dalam kondisi yang penuh tantangan. Implikasi dari penelitian ini adalah intervensi yang dilakukan guru efektif dalam mengatasi kesulitan belajar siswa di masa pembatasan sosial Covid-19.Kata kunci: intervensi guru, kesulitan belajar, kunjungan rumah.